Catazho: Arte rupestre en la amazonía ecuatoriana - Ugalde, María Fernanda (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The registration and inventory of 122 engraved stones in an area of 7.42 km2 is the fi rst approach to pre-Columbian past at Limón- Indanza Canton, province of Morona Santiago, Ecuador. In this area called Catazho, a survey was taken out not only to record the archaeological sites with rock art but it also pretended through experimentation to aim at fi nding the most appropriate technical documentation for recording petroglyphs in a highly humid environment of the Ecuadorian Amazon. It was concluded the frottage on cotton paper and the night photography techniques are the best to reproduce these manifestations of rock art. Preliminary observations in the fi eld of the iconography of this set of petroglyphs indicate the presence of stylistic evolution and abstractions of motifs as part of a compositional grammar, that is, of at least two groups of people linked to the production of this rock art. The article will be available as a PDF in the near future.